Does Securitization Weaken Screening Incentives? - Choi, Dong Beom; Kim, Jung-Eun (Journal of Financial and Quantitative Analysis, 2021)
We test whether lenders’ screening incentives weaken when faced with the possibility of loan sales. We adopt a new measure of lending standards, the processing time for mortgage applications at the loan level, and use the collapse of the nonagency mortgage-backed securities issuance market as a natural experiment. Secondary market liquidity for nonconforming loans decreased significantly at the end of 2007, but the market for securitizing conforming loans did not experience the same breakdown. Following this event, lenders spent significantly more time screening applications for loans larger than the conforming loan limits than for those below the limits. The processing-time gap widened more for banks with lower capital, greater involvement in the originate-to-distribute model, and larger assets.